2022
DOI: 10.1186/s13046-022-02525-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined mitoxantrone and anti-TGFβ treatment with PD-1 blockade enhances antitumor immunity by remodelling the tumor immune landscape in neuroblastoma

Abstract: Background Poor infiltration of functioning T cells renders tumors unresponsive to checkpoint-blocking immunotherapies. Here, we identified a combinatorial in situ immunomodulation strategy based on the administration of selected immunogenic drugs and immunotherapy to sensitize poorly T-cell-infiltrated neuroblastoma (NB) to the host antitumor immune response. Methods 975A2 and 9464D NB cell lines derived from spontaneous tumors of TH-MYCN transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 95 publications
1
9
0
Order By: Relevance
“…As already discussed above, IL-6, released by mononuclear phagocytes upon NB conditioning, and TGF-β1, produced by both immune and tumor cells, inhibit the IL-2-mediated activation of NK cells, through the activation of the STAT3 and SMAD2/3 pathways and suppression of IFN-γ, granzymes, and perforin release. This is in line with the well-documented regulatory role of TGF-β in NK cell activation that emerged from several studies [ 32 , 76 ] supporting the development in NB of preclinical [ 77 ] and clinical studies with combining immunotherapies including the block of the TGF-β activity. Importantly, in NK cells, TGF-β also decreased the expression of activating receptors involved in NB recognition and modified the chemokine receptor repertoire, likely hampering the NK cell recruitment at the tumor sites [ 78 ].…”
Section: Macrophages and Natural Killer Cells Crosstalksupporting
confidence: 83%
“…As already discussed above, IL-6, released by mononuclear phagocytes upon NB conditioning, and TGF-β1, produced by both immune and tumor cells, inhibit the IL-2-mediated activation of NK cells, through the activation of the STAT3 and SMAD2/3 pathways and suppression of IFN-γ, granzymes, and perforin release. This is in line with the well-documented regulatory role of TGF-β in NK cell activation that emerged from several studies [ 32 , 76 ] supporting the development in NB of preclinical [ 77 ] and clinical studies with combining immunotherapies including the block of the TGF-β activity. Importantly, in NK cells, TGF-β also decreased the expression of activating receptors involved in NB recognition and modified the chemokine receptor repertoire, likely hampering the NK cell recruitment at the tumor sites [ 78 ].…”
Section: Macrophages and Natural Killer Cells Crosstalksupporting
confidence: 83%
“…Similarly, noticeable DNA damage in MX-treated bacteria was also observed in RPMI. The efficacy of low-dose MX in conjunction with TGF-β and PD-1 blockade has been demonstrated as a chemotherapeutic intervention for effectively managing tumor growth through the modulation of intratumoral immune cell composition and abundance . Interestingly, a recent study also investigated the immunological activity of MX and reported that MX promoted macrophage recruitment and enhanced the expression of pro-inflammatory cytokines at the wound sites, thus augmenting intracellular bacterial killing .…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of low-dose MX in conjunction with TGF-β and PD-1 blockade has been demonstrated as a chemotherapeutic intervention for effectively managing tumor growth through the modulation of intratumoral immune cell composition and abundance. 34 Interestingly, a recent study also investigated the immunological activity of MX and reported that MX promoted macrophage recruitment and enhanced the expression of proinflammatory cytokines at the wound sites, thus augmenting intracellular bacterial killing. 35 Consistently, our study also found that MX stimulated the upregulation of inflammatory cytokines and triggered an immune response, ultimately leading to the successful eradication of pathogenic bacteria in vivo.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Lucarini et al (Bambino Gesù Children’s Hospital, Rome, Italy) investigated the combination strategy of mitoxantrone and anti-transforming growth factor beta (TGFB1) with programmed cell death-1 (PD-1, also known as PDCD1 ) blockade in neuroblastoma mouse models. They found that the low dose of mitoxantrone by itself was already able to increase IFNγ and granzyme B (GZMB) in CD8 + T cells, which were further increased upon combination with anti-TGFβ and anti-PD-1 blockades 218 . Several papers also revealed a novel connection between anti-cancer agents and the ICD pathway 125 .…”
Section: Preclinical Advancesmentioning
confidence: 99%